Roles and functions of tumor-infiltrating lymphocytes and tertiary lymphoid structures in gastric cancer progression - Yao, Zhiyuan; Li, Gengchen; Pan, Di; Pei, Zichen; Fang, Yan; Liu, Haonan; Han, Zhengxiang (Frontiers in Immunology, 2025)
Gastric cancer (GC), a leading cause of cancer mortality, exhibits profound molecular heterogeneity and immunosuppressive tumor microenvironment (TME) features that limit therapeutic efficacy. This review elucidates the dual roles of tertiary lymphoid structures (TLS) and tumor-infiltrating lymphocytes (TILs) in GC progression. TLS, ectopic lymphoid organs formed under chronic inflammation, correlate with improved survival and immunotherapy sensitivity by fostering effector T/B cell interactions and antigen presentation. Conversely, immunosuppressive TME components like regulatory T cells (Tregs) and tumor-associated macrophages (TAMs) drive immune evasion via cytokine-mediated suppression and checkpoint activation (PD-1/PD-L1). CD8+ T cells exert context-dependent effects, with high infiltration reducing recurrence risk but paradoxically inducing exhaustion in PD-L1-rich microenvironments. Th17 and memory T cells further modulate disease through IL-17-driven angiogenesis and CD45RO+ immune memory dynamics. Multi-omics-based TLS scoring and combinatorial therapies emerge as promising strategies to overcome resistance.